ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT. BANK OF INDIA INDONESIA Tbk PERIODE 2012-2016 - Sepriyanto, Anom Eko (EKONOMIA, 2019)
This study aims to determine: 1) financial performance of PT. Bank of India Indonesia Tbk period 2012 - 2016 is measured from Liquidity Ratio consisting of quick ratio and asset to loan ratio. 2) financial performance of PT. Bank of India Indonesia Tbk for the period 2012-2016 is measured by the Sovability Ratio consisting of primary ratio, risk assets ratio and secondary risk ratio. 3) financial performance of PT. Bank of India Indonesia Tbk for the period 2012-2016 is measured by the Profitability Ratio consisting of gross profit margins and return on loans.The analysis tool used is liquidity ratio which consists of quick ratio and asset to loan ratio. Solvency ratio consisting of primary ratio, risk assets ratio and secondary risk ratio. And profitability ratios consisting of gross profit margins and return on loans.The results of this study indicate: 1) Quick Ratio has decreased in 2012, 2013, 2015 and 2016 and experienced an increase in 2014. 2) Assets To Loan Ratio decreased in 2013, 2014, 2015 and 2016 and experienced an increase in 2012.Â Â 3) Primary Ratio has decreased in 2012, 2013 and 2014 and has increased in 2015 and 2016. 4) Risk Assets Ratio has decreased in 2012, 2013 and 2014 and has increased in 2015 and 2016. 5) Secondary Risk Ratio decreased in 2012 and 2013 and experienced an increase in 2014, 2015 and 2016. 6) Gross Profit Margin experienced a decline in 2012, 2014 and 2015 and experienced an increase in 2013 and 2016. 7) Return On Loans decreased in 2012 and 2014 and experienced a decline in 2013, 2015 and 2016.